Genetic Manipulation of the Cyanobacterium Synechocystis sp. PCC 6803 (Development of Strains Lacking Photosystem I for the Analysis of Mutations in Photosystem II). - Smart, L. B. (1994)
We have taken a genetic approach to eliminating the presence of photosystem I (PSI) in site-directed mutants of photosystem II (PSII) in the cyanobacterium Synechocystis sp. PCC 6803. By selecting under light-activated heterotrophic conditions, we have inactivated the psaA-psaB operon encoding the PSI reaction center proteins in cells containing deletions of the three psbA genes. We have also introduced deletions into both copies of psbD in a strain containing a mutation that inactivates psaA (ADK9). These strains, designated D1-/PSI- and D2-/PSI-, may serve as recipient strains for the incorporation of site-directed mutations in either psbA2 or psbD1. The characterization of these cells, which lack both PSI and PSII, is described.